Perlindungan Hukum Terhadap Penangkapan dan Penahanan Tersangka dalam Perspektif Hak Azasi Manusia - Martono, Martono (Al-Ishlah: Jurnal Ilmiah Hukum, 2020)
This research was conducted to find out the form of the implementation of the rights of suspects at the level of investigation at the Wajo Regional Police Station, as well as what factors influence the implementation of the rights of the suspect at the investigation level of investigations at the Wajo Regional Police Station. This type of research was conducted in the Wajo district police jurisdiction, and data were obtained from in-depth observations, through interviews and then analyzing existing data. The results of the study were analyzed quantitatively by describing data and also using quantitative analysis with descriptive. Protection of Human Rights in the Judicial Act concerning the principles of quick and low-cost justice, the principle of non-discrimination, the principle of presumption of innocence, and guarantees of Human Rights for all Indonesian citizens under the 1945 Constitution. The results obtained by this article are: shows that the implementation of the rights of the suspect at the investigation level investigation at the Wajo Resort Police, in particular the right to obtain legal assistance, the right to be examined immediately, the right to provide information freely, and the right to be informed of his arrest and detention based on the principle of presumption of innocence, based on the results of the study, have been carried out although not optimal due to several factors, namely (1) the quality of investigative Human Resources is still low, the number of personnel is still lacking and is not balanced with the number of cases, investigators who are not professional and (2) the mental attitude of the investigator which is not good, and the level of awareness the law of society which is paternalism so that it causes resignation to law enforcement officers while supporting factors in the form of the increased budget allocated for the settlement of cases. Abstrak:Penelitian ini dilakukan dengan bertujuan untuk mengetahui wujud implementasi hak-hak tersangka pada tingkat penyidikan di Polres Wajo, serta faktor-faktor apa yang mempengaruhi implementasi hak-hak tersangka pada pemeriksaan tingkat penyidikan di Polres Wajo. Tipe penelitian ini dilakukan di wilayah hukum Polres Wajo, dan data diperoleh dari pengamatan yang mendalam, melalui wawancara kemudian menganalisis data yang ada. Hasil penelitian dianalisi secara kuantitatif dengan mendeskripsikan data dan juga menggunakan analisis kuantitatif dengan deskriptif. Perlindungan Hak Azasi Manusia dalam Undang-Undang kehakiman mengenai azas peradilan cepat dan biaya ringan, azas non diskriminasi, azas praduga tidak bersalah, dan jaminan Hak Azasi Manusia bagi seluruh warga Negara Indonesia berdasarkan Undang- undang Dasar 1945. Hasil yang diperoleh oleh artikel ini adalah: menunjukkan bahwa wujud implementasi hak-hak tersangka pada pemeriksaan tingkat penyidikan di Kepolisian Resort Wajo, khususnya hak memperoleh bantuan hukum, hak untuk segera diperiksa, hak untuk memberikan keterangan secara bebas, dan hak untuk diberitahukan penagkapan dan penahanannya berdasarkan azas praduga tak bersalah, berdasarkan hasil penelitian, sudah dilaksanakan meskipun belum optimal yang disebabkan karena beberapa faktor, yaitu (1) kualitas Sumber Daya Manusia penyidik yang masih rendah, jumlah personil yang masih kurang dan tidak seimbang dengan banyaknya perkara, penyidik yang tidak profesional dan (2) sikap mental penyidik yang kurang baik, serta tingkat kesadaran hukum masyarakat yang paternalisme, sehingga menyebabkan sikap pasrah kepada aparat penegak hukum, sedangkan faktor pendukung berupa meningkatnya anggaran yang dialokasikan untuk penyelesaian perkara.